Biological soil crusts: New genera and species of Cyanobacteria from Brazilian semi-Arid regions - Lim, Náthali Maria MacHado De [UNESP]; Branco, Luis H. Z. [UNESP] (Magnolia Press, 2020)
In the uppermost millimeters of soils is commonly found a thin layer of cryptobiotic organisms, including cyanobacteria, microalgae, lichens, mosses, fungi, bacteria and archaea. These communities are called Biological Soil Crusts (BSCs) or biocrusts and perform important ecological functions, mainly attributed to their capacity of providing soil stability and incorporate nutrients through nitrogen and carbon fixation. Among all the organisms found in the biocrusts, the filamentous cyanobacteria Microcoleus vaginatus and M. steenstrupii are the best studied soil colonizers. The genus Microcoleus is considered complex and has been showing close relation with some species of Phormidium. The poor understanding about these two genera is a limit to the description of the real composition of biocrusts and can generate underestimations in the diversity community and the use of wrong organisms in applied projects (e.g. environmental restoration). This work studied eight cyanobacterial populations from Brazilian BSCs sampled in the Caatinga biome. The populations presented Microcoleus-like and Phormidium-like morphologies, but the phylogenetic analyses based on 16S rRNA gene sequences showed that they represent three new genera and six new species of filamentous cyanobacteria associated to the cryptic genera, they are Pycnacronema caatingensis sp. nov., Pycnacronema edaphica sp. nov., Gracilinea arenicola gen. et sp. nov., Marmoreocelis xerophila gen. et sp. nov., Konicacronema caatinguensis gen. et sp. nov. and Trichocoleus caatingensis sp. nov. The generic name and specific epithets of the new taxa are proposed according to the provisions of the International Code of Nomenclature of algae, fungi, and plants.